A variable dimensional chaotic map-based medical image encryption algorithm with multi-mode - Bahbibi Rahmatullah (Tanjung Malim, 2023)
A variable dimensional chaotic map-based medical image encryption algorithm with multi-mode by Bahbibi Rahmatullah